2008
DOI: 10.1063/1.3050324
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nanocluster-sensitized emission from erbium: The role of stress in the formation of silicon nanoclusters

Abstract: Erbium-doped silicon-rich silicon oxide films deposited by plasma enhanced chemical vapor deposition suffer from compressive stress as deposited, which converts to a large tensile stress on annealing due to the release of hydrogen. Although the cracking that results from this stress can be avoided by patterning the films into ridges, significant stress remains along the ridge axis. Measurements of erbium photoluminescence sensitized by silicon nanoclusters in stressed and relaxed films suggest an important rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…the thickness [18,29], (ii) the stress-induced effect which affects the phase separation and then the formation of Si-nc. [19] Concerning the PL properties, consistent results were obtained, as shown by the typical spectra of Fig. 3 for the thicker sample deposited at RT.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…the thickness [18,29], (ii) the stress-induced effect which affects the phase separation and then the formation of Si-nc. [19] Concerning the PL properties, consistent results were obtained, as shown by the typical spectra of Fig. 3 for the thicker sample deposited at RT.…”
Section: Discussionsupporting
confidence: 68%
“…ness dependence in terms of nucleation barrier for Si nanoclusters [18] or stress-induced promotion of Si-nc formation [19]. This study aims at examining the influence of the layer thickness on the composition, microstructure and optical properties of SRSO: Er thin films deposited by magnetron co-sputtering.…”
Section: °C-depositionmentioning
confidence: 99%
“…Although the material composition is intentionally identical for all samples, PL intensity does not depend linearly on the film thickness. This is due to the fact that difference in thickness leads to different stress in the samples, which affects nucleation and growth of Si-ncs during thermal treatment [9,10]. The inset shows time constants of PL decay.…”
Section: Methodsmentioning
confidence: 99%
“…This fact has precluded the achievement of siliconbased optoelectronic systems for a long time. Over the last few years, several works have shown that it is possible to obtain light emission from silicon-based materials by doping with rare earth elements [1,2], low-dimensional [3,4] and stressed systems [5]. Another approach is through the synthesis of non-stoichiometric silicon dioxide [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%